2012
DOI: 10.5038/1827-806x.41.2.5
|View full text |Cite
|
Sign up to set email alerts
|

Duality of terrestrial subterranean fauna

Abstract: Terrestrial animals in subterranean habitats are often classified according to their degree of morphological or ecological specialization to the subterranean environment. The commonly held view is that, as distance into a cave increases, the frequency of morphologically specialized, i.e., troglomorphic, species or ecological specialization will increase. We tested this hypothesis for the fauna in 54 caves in Slovenia-the classical land for subterranean biology. We found that there exist two ecologically well s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
42
1
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 51 publications
(48 citation statements)
references
References 26 publications
2
42
1
1
Order By: Relevance
“…Although karst ecosystems are usually diverse and are very important in many aspects of ecological research (e.g. Cardoso, 2012;Novak et al, 2012), there are still many open questions about how karst surfaces will change under future global warming.…”
Section: Introductionmentioning
confidence: 99%
“…Although karst ecosystems are usually diverse and are very important in many aspects of ecological research (e.g. Cardoso, 2012;Novak et al, 2012), there are still many open questions about how karst surfaces will change under future global warming.…”
Section: Introductionmentioning
confidence: 99%
“…Such a distribution is also true for all the species under study, which are most abundant in the upper 10 m beneath the surface (Novak et al 2012). Gibert (1986) found that dissolved organic carbon is the most important among abiotic carbon sources in subterranean water.…”
Section: Discussionmentioning
confidence: 86%
“…In contrast to the general assumption and our hypothesis, in Central European caves, non-troglobiotic taxa contribute very little to the deep troglobiotic species. Additionally, predated individuals contributed maximally 0.15% C. This low carbon input might be the main reason why a major group of troglobionts inhabit shallow subterranean habiinhabit shallow subterranean habitats (Novak et al 2012).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations